METHOD OF THE AIRCRAFT CONTROL RECONFIGURATION WHEN UNEXPECTED SITUATION APPEARS DURING FLIGHT - Shevchuk, Dmitriy (Proceedings of National Aviation University (archive), 2014)
Comparative analysis of the ICAO statistics showed that 35% of the aircraft losses associated with failures and damages of automatic control systems, mainly with failures of drives and external damage of tours and controllers. Classification of approaches to reconfigurable flight control systems is shown. The aim of this work is to develop method of reconfiguration to save the stability and controllability of the aircraft during the collisions with mechanical, biological and electrical elements.